Pelaksanaan Program “Madrasah Lancar Baca Al-Qur’an” di MTSN 3 Kota Pariaman - Putri Zahara Mudasir; Puti Andam Dewi; Eli Fitri (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was motivated by the school's concern about students' ability to read the Al-Qur'an at MTsN 3 Kota Pariaman which was still not fluent, this was known from the tahfiz program which was carried out every morning. Some students who are tahfiz leaders at the front are not fluent in reading the Koran and do not understand the correct rules of tajwid, especially new students. This makes it difficult for students to memorize and study the Al-Qur'an, where one of the subjects at this school is tahfiz lessons. This raises concerns from the school. One of the solutions designed by the school to overcome this problem is to implement